Intestinal type villous adenoma of the renal pelvis - Hudson, Jill; Arnason, Thomas; Merrimen, Jennifer L.O.; Lawen, Joseph (Canadian Urological Association Journal, 2013)
Intestinal type villous adenomas are uncommon in the genitourinary tract. Most reported cases have been located in the urinary bladder or urachus. Villous adenoma arising in the renal pelvis or ureteris very rare. We present a case of an 81-year-old female who presented with difficulty voiding and mucosuria. A computed tomography scan identified right-sided hydronephrosis, renal parenchymal atrophy, nonobstructing calculi and a lower pole renal mass. She underwent open right nephrectomy. Histopathologic examination of the kidney revealed an intestinal type villous adenoma of the renal pelvis with high-grade dysplasia and focal areas suspicious for invasive adenocarcinoma. We review the four previously reported cases of intestinal type villous adenoma in the renal pelvis and discuss diagnosis and management of this unusual neoplasm.